Validation of the Adapted Picture Version of the Pyramids and Palm Trees Test for Thais with Dementia - Duangkamol Singwicha; Chatchawan Rattanabannakit; Saowalak Hunnangkul; Atthapon Raksthaput; Sunisa Chaichanettee; Natthamon Wongkom; Pathitta Dujada; Vorapun Senanarong (Siriraj Medical Journal)
Objective: We aimed to validate Pyramids and Palm Trees test (PPT) in dementia cohort and explore reliability measurement of this test.